'A DISCOURSE [. . .] OF DENMARKE', 1588. (18th December 2015) - Unknown
Abstract : A discourse touching ye present estate and gouuernement of the kingdomes of Denmarke and Norwegen, with a description of the said realmes, and Dominions appertayninge vnto them. written in September Anno 1588.